Bignay (Antidesma Bunius) Leaf Extract Stands as an Organic Pesticide against Rice Black Bugs (Scotinophara Coarctata) - Jeune Aiyana Zophie Latiza; Ashley Claire Pasawilan; Goji Gacoscos; Dave Lesther Bangeles; Charles Godwin Caas; Anamarie Valdez; Hassanal Abusama (ASEAN Journal of Science and Engineering, 2022)
This research aimed to sought solutions to the growing problems of rice black bugs (Scotinophara coarctata) damaging the rice crops of farmers. This study used an experimental method to determine which solution is effective against rice black bugs. Bignay (Antidesma bunius) leaves were collected, cut, soaked in water, crushed using a mortar and pestle, and extracted using a thin cloth. The extracts of the leaves were then placed in 4 different concentrations in bottles. 6 bugs were soaked in each solution, respectively, but with different periods (3, 5, and 10 min). We found that the extract is lethal towards black bugs since it has anti-bacterial activity, even though it damaged the rice crops. Bignay fruit was intended to be utilized as another variable, but due to the weather, fruits were not yet visible in the Bignay tree. We concluded that the thickness of the solution served as the main reason why the rice black bugs died. The result of this study can be utilized to address the rising problems caused by rice black bugs.